Exploration of Ethnomathematics in Kidal Temple Ornaments For Geometry Learning - Umam, Akromal; Handayani, Ucik Fitri (Tematik : Jurnal Konten Pendidikan Matematika, 2025)
Learning that relates material to the context of students' lives and culture will make it easier for students to interpret learning. One of the sciences that can connect education and culture is ethnomathematics. Education is important in the process of cultural inheritance and culture is important to be implemented in learning. The cultural heritage of Singosari Kingdom is in the form of artifacts and also human activities. The influence of local culture adapts the temple, so the design of temples in Indonesia varies. This research aims to explore and describe the concept of geometry that is applied and developed in the decorative ornaments of Kidal Temple. The type of research used is qualitative research with an ethnographic approach. Data will be collected through interviews, observation and documentation. The data analysis techniques used are domain analysis and taxonomy analysis. The results showed the existence of the concept of mathematical geometry applied to the architecture of the Kidal Temple building. The ornaments that decorate Kidal Temple implement mathematical concepts. The mathematical concept in the ornament represents the concept of flat shapes in the geometric material. The concept of rectangular and circular flat shapes is found in the medallion ornaments. The concept of triangular flat geometry is found in the tumpal ornament on the roof of the temple, then in the sulur or floral ornament found at the foot of the temple, the concept of reflection or mirroring of the x-axis is applied.